Demystifying Kashmir - Behera, Navnita Chadha; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2006)
"Traces Kashmir history from the prepartition India to the current-day situation. Provides an analysis of the philosophical underpinnings and the local, bilateral, and international dynamics of the key players involved in this conflict. Conclusion focuses on the parameters, players, politics, and prognosis of the ongoing peace process in Kashmir"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Jammu and Kashmir (India) -- Politics and government; Jammu and Kashmir (India) -- History -- Autonomy and independence movements; Azad Kashmir -- Politics and government; Electronic books